Decoupling the sequence of dielectric breakdown in single device bilayer stacks by radiation-controlled, spatially localized creation of oxide defects - Aguirre, Fernando Leonel (2021)
The breakdown (BD) sequence in high-K/interfacial layer (HK/IL) stacks for time-dependent dielectric breakdown (TDDB) has remained controversial for sub-45 nm CMOS nodes, as many attempts to decode it were not based on proper experimental methods. Know-how of this sequence is critical to the future design for reliability of FinFETs and nanosheet transistors. We present here the use of radiation fluence as a tool to precisely tune the defect density in the dielectric layer, which jointly with the statistical study of the soft, progressive and hard BD, allow us to infer the BD sequence using a single HfO2–SiOx bilayered MOS structure.